(3GdJLQHI GdLRGFQjIs - (3eOfj(B, (3Hf TgQIs ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2008)
-(3adSaI HQfGeL GdGUdGM GdGbJUGOj GdPj jDGRQhg UfOhb GdfbO GdOhdj (B-(3GdKfGFjI GdYGdejI hSjGSI GdGUdGM GdGbJUGOj (B-(3feGPL GdGUdGM GdGbJUGOj GdQFjSjI GdebJQMI ef NHQGA UfOhb GdfbO GdOhdj(B-(3GdLRGFQ hUfOhb GdfbO GdOhdj(B-(3JMdjd JWhQ GdJTZjd aj GdLRGFQ(B(1966-1999) -(3BKGQ SjGSI GdGUdGM Ydi eSJhi GdJTZjd hGdHWGdI (B-(3CSHGH eTcdI GdHWGdI aj GdLRGFQ hJbjje SjGSGJ YdGLgG (B-(3GdELQGAGJ GdeQGabI dHQfGeL GdGUdGM GdGbJUGOj ddJNaja ef BKGQgs
((3EbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdEUdGM GdEbJUGOjs; (3JTZjds; (3SjGSI GdJTZjds; (3UfOhb GdfbO GdOhdjs